The Puzzle of Informational Efficiency & Macroeconomic Variables: A Comparative Evidence in Shari’ah Stock Markets of Pakistan viz-a-viz Malaysia - Shehryar, Muhammad; Qamar Abbas; Muhammad Nouman Anser; Kashif Raza (iRASD Journal of Economics, 2022)
The present study examines the weak-form informational efficiency of the Shari’ah stock market of Pakistan and Malaysia. For this purpose, the study uses the daily index price data of the KSE Meezan Index (Pakistan) & FTSE Malaysia EMAS Shariah Index (Malaysia) for the time span starting from 1st July 2009 to 30th June 2019. By employing a more robust test namely Automatic Portmanteau Test (AQ Test) through testing the Martingale Difference Hypothesis, this study finds that KSE Meezan Index (KMI-30) was informationally efficient (weak-form) whereas FTSE Malaysia EMAS Shariah Index was not weak-form of efficient. Further, this research investigates the long-run relationship viz-a-viz short-run relationship among the returns of both Islamic stock markets and three macroeconomic variables (Exchange Rate, Inflation Rate, Interest Rate) of both said countries. In this connection, this study employs the Philips-Perron Test for stationary analysis, Johansen co-integration test, Vector Error Correction Model on the monthly time series data for the same said sample period. The statistical findings show that returns of both Shari’ah stock markets have a long-run association with said macroeconomic variables and have the co-integration or long-term association with long-run causality running from macroeconomic variables to the return of the Islamic stock market in both sample countries but the short-run association viz-a-viz short-run causality is not found.